The Hazardous Effect of Short Birth Interval on Physical Growth. A 4 - Case Study - Aliamram Rasjid; Rachmat Kurdi; Sudiyanto Sudiyanto; Zainulbahri Noer (Indonesian Pediatric Society, 1979)
A case study of the hazardous effect of short birth interval upon the physical growth of four siblings of a middle-class, well-educated family has been undertaken. For the purpose of the study the records of four siblings were retrospectively evaluated to the age of 18 months. This study revealed that short interval between birth and the next conception exerted great influence on the physical growth as shown by the weight curve.